Bridging the gap: community health workers as a vital link in humanitarian medical responses - Nally, Cora P.; Van de Voorde, Patrick; Temmerman, Marleen; Koroma, Adama; Mitchell, Monique; Adam, Mary B. (Frontiers in Disaster and Emergency Medicine, 2025)
Community Health Workers (CHWs) have proven essential in improving health outcomes and building community trust and their role in humanitarian emergency medical responses warrants further study. We illustrate this point with two case studies, the integration of community health workers into Mobile Medical Teams [MMTs] in both The Bahamas and Sierra Leone. CHWs in these examples came to the forefront of addressing community mistrust for external medical teams, health communication efforts and patient follow-up care. In Sierra Leone, this program resulted in a 32% rise in referrals to established health services. By exploring these contexts, the paper provides a new framework for enhancing humanitarian responses through CHWs, outlining the strategic, logistical, and cultural benefits of such an approach. This research suggests that integrating CHWs with MMT's can bolster health outcomes, especially in communities affected by political instability, natural disasters, and resource limitations. The paper ends by providing policy implications and recommendations for further research on the use of CHWs during a range of emergency contexts.